Lipedema and its Main Characteristics: A Literary Review (Global Journal of Medical Research, 2023)
Lipedema is defined as a genetic disorder that affects the mass of adipose tissue and its distribution due to abnormal deposition of fat in the buttocks and legs bilaterally The characteristic symptoms are pain tightness and a tendency to hematomas The onset of lipedema is typically triggered by hormonal changes puberty pregnancy menopause stress This condition affects almost exclusively women leading to considerable disability impaired daily functioning and psychosocial distress A survey carried out in 2022 by the Department of Vascular Surgery of the Amato Institute revealed that the prevalence of lipedema in the population of Brazilian women is 12 3 Research on this disease is still scarce considering that it has a difficult diagnosis heterogeneous picture and lack of objective measurement instruments to characterize the conditions The cause of this chronic progressive condition is still unexplained but there are some hypotheses about its pathophysiology As it usually manifests itself in periods of hormonal change and is characterized by a disproportionate distribution of body fat this condition is believed to be mediated by estrogen Thus through this study we seek to clarify the general aspects pathogenesis diagnosis treatment and complications of lipedema